Ferritin reactions: Direct identification of the site for the diferric peroxide reaction intermediate - Xiaofeng Liu; Elizabeth C. Theil (2004)
Ferritins managing iron–oxygen biochemistry in animals, plants, and microorganisms belong to the diiron carboxylate protein family and concentrate iron as ferric oxide ≈10 14 times above the ferric K s . Ferritin iron (up to 4,500 atoms), used for iron cofactors and heme, or to trap DNA-damaging oxidants in microorganisms, is concentrated in the protein nanocage cavity (5–8 nm) formed during assembly of polypeptide subunits, 24 in maxiferritins and 12 in miniferritins/DNA protection during starvation proteins. Direct identification of ferritin ferroxidase (F ox ) sites, complicated by multiple types of iron–ferritin interactions, is now achieved with chimeric proteins where putative F ox site residues were introduced singly and cumulatively into an inactive host, an L maxiferritin. A dimagnesium ferritin cocrystal model guided site design and the diferric peroxo F ox intermediates ( A at 650 nm) monitored activity. Diferric peroxo formation in chimeric and WT proteins had similar K app values and Hill coefficients. Catalytic activity required cooperative ferrous substrate binding to two sites A (E, EXXH) and B (E, QXXD). The weaker B sites in ferritin contrast with stronger B sites (E, EXXH) in diiron carboxylate oxygenases, explaining diferric oxo/hydroxo product release in ferritin vs. diiron cofactor retention in oxygenases. Codons for Q/H and D/E differ by single nucleotides, suggesting simple DNA mutations relate site B diiron substrate sites and diiron cofactor sites in proteins. The smaller k cat values in chimeras indicate the absence of second-shell residues important for ferritin substrate–product channeling that, when identified, will outline the entire iron path from ferritin pores through the F ox site to the mineral cavity.